Peningkatan Soft Skill Melalui Program Pelatihan Bebras Challenge Untuk Meningkatkan Kemampuan Computational Thinking Siswa SMK - Nuril Huda; Ika Wahyu Pratiwi; Ery Sugito; Ahmad Fadhil Imran; M. Miftach Fakhri (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2023)
ABTRACT The purpose of this service activity is to improve the Computational Thinking (CT) skills of vocational students through the Bebras Challenge training program. Since its introduction by Wing in 2006, CT has become a major focus in science, technology, engineering and math (STEM) education. In the context of this service activity, some of the problems identified involved students' lack of proficiency in CT, ignorance of Bebras Challenge activities, and lack of promotion of the use of the internet in CT learning. This training was carried out by applying lecture methods, question and answer sessions, and exercises/practices. The results of the implementation of this service activity show that students can apply Computational Thinking to solve everyday problems. This service method proved effective in motivating students and teachers to actively use technology as a CT learning tool. In addition, this training helps students to better understand the types of challenges faced in Bebras and the concept of CT.